Enduring Legacies of Agriculture: Long-term Vegetation Impacts of Ancestral Menominee Agriculture, Wisconsin, USA - McLeester, Madeleine; Anastasio, Alison E.; Grignon, Jeff (Ethnobiology Letters, 2023)
Agriculture significantly reshapes soils and ecology, often with lasting ecological impacts. For over a millennium, the Menominee Indian Tribe of Wisconsin have practiced maize agriculture in the upper Great Lakes. Though the vast majority of ancestral Indigenous agricultural sites have been destroyed in the American Midwest, the Menominee have documented numerous archaeological, raised garden bed sites at their Reservation, enabling an investigation into the lasting vegetation impacts of ancestral Menominee agricultural practices. Here, we report findings from our pilot vegetation surveys of three ancestral raised garden bed sites. Results show that all sites surveyed are high quality ecosystems. We observed differences in species richness between agricultural and non-agricultural places, although findings varied based on location. Overall, our surveys illustrate the complexity of these anthropogenic, biologically diverse landscapes shaped by past and contemporary Menominee land use and illustrate how today’s ecology is in part an enduring legacy of past practices.